Contribution of ultrasonic surface rolling process to the fatigue properties of TB8 alloy with body-centered cubic structure. (20th January 2021) - Liu, Dan; Liu, Daoxin; Guagliano, Mario; Xu, Xingchen; Fan, Kaifa; Bagherifard, Sara
Abstract: The effect of ultrasonic surface rolling process (USRP) as a severe plastic deformation technology was investigated on the evolution of microstructure, residual stress and surface morphology of TB8 alloys with body-centered cubic structure. Stress-controlled rotating-bending fatigue tests indicated increased fatigue strength in USRP samples prepared using different number of passes compared to the base material, which was attributed to the presence of gradient structure surface layers. Five subsequent USRP passes resulted in the highest fatigue strength, due to the optimal surface properties including higher extent of grain refinement, larger compressive residual stresses, "smoother" surface morphology and increased micro-hardness. However, the effect of USRP technology on improving fatigue strength of TB8 alloy was not significant in comparison with that of other titanium alloys (for example, Ti6Al4V), which was attributed to the notable surface residual stresses relaxation revealed from measurements on post-fatigued USRP samples. Electron backscatter diffraction analysis confirmed that fatigue crack initiation occurred in the larger grains on the surface with high Schmid factor. Small cracks were found to propagate into the core material in a mixed transgranular and intergranular mode. Further analysis indicated that grain growth existed in post-fatigued USRP-treated TB8 samples and that the average geometrically necessary dislocations value reduced after fatigue loading.